Exploring the Factors Contributing to Poor Academic Performance among Senior Secondary School Students: A Case of Wamakko Local Government Area, Sokoto State - Muhammad Sani, Kamal; Mamman Adam, Maryam; Garba Nadama, Safiya; Abdullahi Muhammad, Fatima; Sani Udu, Madina; Mohammed , Fatima; Yusuf Datti, Abdulmumini (EduLine: Journal of Education and Learning Innovation, 2024)
The principal aim of this research paper was to examine the social, psychological, and economic factors that contribute to poor academic performance (PAP) among senior secondary school students with special reference to Wamakko Local Government Area (WLGA), Sokoto State, Nigeria. We utilized a semi-structured questionnaire, in-depth interviews (IDI), and focus group discussions (FGD) to collect data from 220 enrolled senior secondary school students, 10 teachers, and 5 school principals. The statistical results revealed that numerous factors harm the academic performance of students in secondary schools. The results indicate that poor time management (75%), language barriers (74%), and financial constraints (70%) adversely affect the academic performance of senior secondary school students in WLGA. The study concludes with suggestions aimed at improving students’ academic performance.